Bicycle shoe insoles and their effect on lateral knee movement, leg muscle activation patterns, and performance in experienced cyclists - Meyers, A. C.; Caldwell, E. C.; Hirsch, J.; Eltoukhy, M.; Jacobs, K. A.; Pohlig, R.; Signorile, J. (Journal of Science and Cycling, 2015)
Introduction: Riders contact their bicycles at three points: hands, hips, and foot-shoe-cleat-pedal (FSCP) interface (Figure 1). Three techniques are used to achieve fit: experienced-based direct observation, technology-assisted indirect observation, and anthropometrically-based formula fitting (Hogg, 2012). No technique takes full advantage of knowledge concerning the FSCP interface and its potential effects on the mechanics of the legs. Orthotic insoles are an intervention used to correct running mechanics (McMillan & Payne, 2008; Eng & Pierrynowski, 1994), but have received little attention in relation to cycling. This study tested the hypothesis that orthotic insoles in cycling shoes would alter the pedaling mechanics, muscle activity, and submaximal efficiency of healthy, experienced, male cyclists. Additionally, it was hypothesized that the insole that allowed the lowest level of lateral knee movement would produce the greatest improvements in these variables, and be related to arch height